Effect of one-to-one versus group counseling on uptake of postpartum contraception in selected hospitals in Ghana: A prospective cohort study - Asah-Opoku, K.; Mumuni, K.; Ameme, D.K.; Mohammed, A.G.; Samba, A.; Nkyekyer, K. (International Journal of Gynecology and Obstetrics, 2023)
Objective: To compare the effect of one provider to one client counseling and one provider to a group client counseling on the uptake of postpartum contraception. Methods: This was a hospital-based prospective cohort study among women attending a postpartum clinic at Korle-Bu Teaching Hospital and Greater Accra Regional Hospital. Postpartum mothers were recruited daily from April 1, 2017 to November 28, 2017. Mothers from this cohort that used a contraceptive method within a year postpartum were determined at 3, 6, 9, and 12 months after recruitment. A P value of less than 0.05 was considered statistically significant for all analyses. Results: Of 982 women surveyed, contraceptive uptake among women who received one-to-one counseling was 306/600 (51.0%) and that for women who received group counseling was 48/382 (12.6%) (P < 0.001). Factors associated with contraceptive uptake during postpartum period were: one-to-one counseling (adjusted odds ratio [aOR] 7.05, 95% confidence interval [CI] 4.94–10.07), mothers' age (aOR 0.95, 95% CI 0.91–0.98), being single (aOR 0.54, 95% CI 0.35–0.85), cohabiting (aOR 0.39, 95% CI 0.22–0.69), and previous use of contraception (aOR 1.55, 95% CI 1.12–2.15). Conclusion: One-to-one counseling was associated with a significantly greater uptake of contraception during the postpartum period compared with group counseling. Other factors associated with uptake were age, marital status, and history of contraceptive use.
Research Article
Keywords: contraceptives; counseling; family planning